2011
DOI: 10.1111/j.1365-2672.2011.05015.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulent Escherichia coli O157 strains using multiplex PCR and single base sequencing for SNP characterization

Abstract: Aims:  To compare 167 Norwegian human and nonhuman Escherichia coli O157:H7/NM (nonmotile) isolates with respect to an A/T single nucleotide polymorphism (SNP) in the tir gene and to detect specific SNPs that differentiate STEC O157 into distinct virulence clades (1–3 and 8). Methods and Results:  We developed a multiplex PCR followed by single base sequencing for detection of the SNPs, and examined the association among SNP genotype, virulence profile (stx and eae status), multilocus variable number of tandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Consequently, like with the Q gene variants, bovine isolates were dominated by isolates carrying only stx 2c (86%), while this frequency was only 37% among clinical isolates. Similar patterns were reported by recent Norwegian (18) and Japanese (26) studies. Epidemiological studies have revealed that stx 2a is more strongly associated with clinical isolates and causes more severe symptoms than stx 2c (1,4,21,36).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, like with the Q gene variants, bovine isolates were dominated by isolates carrying only stx 2c (86%), while this frequency was only 37% among clinical isolates. Similar patterns were reported by recent Norwegian (18) and Japanese (26) studies. Epidemiological studies have revealed that stx 2a is more strongly associated with clinical isolates and causes more severe symptoms than stx 2c (1,4,21,36).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the tir(A255T) polymorphism assay confirm earlier findings of an overrepresentation of the tir(255T) variant among human clinical isolates of STEC O157 isolates and an approximately equal distribution of both variants among bovine isolates (6,18). The reason for the specific association of human clinical isolates with tir(255T) is unknown.…”
Section: Discussionsupporting
confidence: 76%
“…Argentina has a high clade 8 prevalence among E. coli O157:H7 in cattle (ϳ50%) and even higher among human cases (ϳ80%) (25), together with an extremely high HUS incidence (26) compared to countries with little or no clade 8 strains. A few studies on clade 8 have been performed in Europe; in a set of Norwegian isolates investigated by Haugum et al (27), clade 8 occurred more commonly in human than in nonhuman sources but was not significantly associated with HUS (27). A recent study comparing cattle and human isolates of E. coli O157:H7 from the Netherlands found no specific association of clade 8 with strains of human clinical origin (28).…”
Section: Resultsmentioning
confidence: 99%
“…The production of large numbers of low cost reads from these sequencing platforms makes these next generation sequencing technologies to be applied for quick de novo assemblies of out breaking pathogenic bacterial and viral genomes and a quick analysis to determine its identity as done for human influenza A viruses and virulent Escherichia coli O157 strains. 34,35 Moving forward these automated sequencing technologies will play a crucial role in detection and diagnostics of pathogens of future outbreaks.…”
Section: Resultsmentioning
confidence: 99%